2023
DOI: 10.3390/ijerph20021356
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Influence of Green Marketing Communication in Consumers’ Green Purchase Behaviour

Abstract: This study aims to explore whether consumers’ attention to companies’ green marketing communication influences their green purchase behaviour. It also analyses the importance of consumers’ characteristics, namely gender, education, and green attitudes, in their attention to companies’ green marketing communication. An online survey was carried out on the population residing in Portugal over 18 years of age, allowing us to collect 690 valid responses. Data analysis techniques including descriptive analyses, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 105 publications
(130 reference statements)
3
24
0
2
Order By: Relevance
“…Correia et al (2023). However, PS and PV have no significant relationship with GB, which is in line with the results ofWang et al (2019).…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Correia et al (2023). However, PS and PV have no significant relationship with GB, which is in line with the results ofWang et al (2019).…”
supporting
confidence: 86%
“…Based on this result, it can be inferred that the higher the cost of the responses (that the students are expected to do), the lower the GB. This result is consistent with the results of Keshavarz and Karami (2016), Wang et al (2019), Shafiei and Maleksaeidi (2020), Sousa et al (2022b) and Correia et al (2023) and inconsistent with the results of Bijani et al (2022). In this regard, it can be concluded that in encouraging students to GB, different responses should be evaluated and analyzed in terms of the costs that may be incurred.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The four independent variables used in our model were (i) Attitude (ATT) [ 9 , 17 ], (ii) Subjective Norm (SN) [ 9 , 67 ], (iii) Perceived Behavioral Control (PBC) [ 9 , 74 ], and (iv) Environmental Consciousness (EC) [ 9 , 75 , 76 ], and the dependent variable was (v) Environmental Responsibly Purchase Intention (ERPI) [ 9 ]. Finally, the moderating variable was age, using generations X, Y, and Z.…”
Section: Methodsmentioning
confidence: 99%
“…Environmentally responsible behavior can facilitate improving the environment and advancing a sustainable society [ 17 , 18 , 19 ]. In this context, emergent research findings have linked the effects of COVID-19 on consumers’ perceptions, environmental awareness, or/and purchase intention [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%